Socialization of water activity therapy to stabilize blood sugar levels for people with diabetes mellitus - Siti Khadijah; Suryanti Suryanti; Hartono Hartono (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
The prevalence of Diabetes Mellitus is still high in society, and in its therapy, there are 5 main pillars, namely diet, medicine, education, regular monitoring of blood sugar, and exercise. The purpose of this community service is to provide socialization of water activity therapy to stabilize blood sugar levels. The method is carried out by providing socialization with 2 stages, including socialization by practicing on land and the second stage of practicing in the swimming pool, then an evaluation is carried out. The results of people with diabetes Mellitus in Persadia are very enthusiastic, the exercise can be done lightly without having to be able to swim and have a positive impact on health, especially being able to stabilize blood sugar levels, and the knowledge of people with diabetes mellitus (DM) increases. Conclusion water activity therapy is a new sport that gives the benefit of stabilizing blood sugar vessels. The implication of this program is that water activity therapy when carried out in institutions or groups that accommodate people with DM routinely controlled blood sugar, and people with DM life can be better.